THE ROLE OF MODERN BIOLOGY CLASSROOMS IN SECONDARY SCHOOLS IN INCREASING THE EFFECTIVENESS OF LESSONS - Ruzieva Gulsara Temirkulovna (Scholar Express Journal, 2021)
The article provides recommendations for the creation of a modern biology room in order to increase the interest of students in biology in secondary schools, to develop their knowledge, skills and abilities
Keywords: electronic board; computer; aesthetic requirements; hygiene requirements